2016
DOI: 10.1038/srep37002
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of proenkephalin and prodynorphin mRNAs in the nucleus accumbens of compulsive methamphetamine taking rats

Abstract: Addiction is associated with neuroadaptive changes in the brain. In the present paper, we used a model of methamphetamine self-administration during which we used footshocks to divide rats into animals that continue to press a lever to get methamphetamine (shock-resistant) and those that significantly reduce pressing the lever (shock-sensitive) despite the shocks. We trained male Sprague-Dawley rats to self-administer methamphetamine (0.1 mg/kg/infusion) for 9 hours daily for 20 days. Control group self-admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 56 publications
3
17
0
Order By: Relevance
“…Similar to our previous reports (Cadet et al, 2016;Krasnova et al, 2017;Torres et al, 2017), the introduction of footshocks allowed for the separation of rats that had escalated their oxycodone intake into (1) shock-resistant (SR) animals that continue to press the lever slightly less than before and (2) shock-sensitive (SS) that markedly decreased their intake of the drug (Figure 1D). Fifty five percent (55%) of the oxycodone SA rats were classified as SR while 45% were denoted SS animals.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…Similar to our previous reports (Cadet et al, 2016;Krasnova et al, 2017;Torres et al, 2017), the introduction of footshocks allowed for the separation of rats that had escalated their oxycodone intake into (1) shock-resistant (SR) animals that continue to press the lever slightly less than before and (2) shock-sensitive (SS) that markedly decreased their intake of the drug (Figure 1D). Fifty five percent (55%) of the oxycodone SA rats were classified as SR while 45% were denoted SS animals.…”
Section: Resultssupporting
confidence: 75%
“…It is also possible that rats with differential OPRM1 SNPs might respond differential to contingent footshocks in terms of oxycodone SA and resulting changes in IEG expression during the punishment phase of the study, with the end result being abstention from lever pressing in order to avoid footshocks. Differential alterations in the expression of several mRNAs and proteins have previously been reported in the dorsal striatum of the SR and SS phenotypes in the case of methamphetamine SA and footshocks (Cadet et al, 2016;Torres et al, 2017). Therefore, we had predicted that the SR rats might show acute increased expression of some IEGs because they were taking oxycodone just 2-h before they were euthanized.…”
Section: Discussionmentioning
confidence: 96%
“…Pre-clinical studies have used footshock punishment of a drug-reinforced action in laboratory animals to study compulsive use (Grove and Schuster, 1974; Smith and Davis, 1974; Spealman, 1979; Panlilio et al, 2003; Deroche-Gamonet et al, 2004), although other methods are also used, including quinine adulteration in alcohol (Wolffgramm, 1991; Hopf et al, 2010), and intravenous histamine injection (Goldberg, 1980). One relatively consistent finding in more recent studies is that a sub-group of rats persist with drug self-administration in the face of punishment (Deroche-Gamonet et al, 2004; Vanderschuren and Everitt, 2004; Pelloux et al, 2007; Seif et al, 2013; Cadet et al, 2016a; Cadet et al, 2016b). Studies have shown that extended access to cocaine is a necessary factor leading to compulsive cocaine seeking in a sub-population of rats (Vanderschuren and Everitt, 2004; Pelloux et al, 2007).…”
Section: Introductionsupporting
confidence: 58%
“…Within this same region, we also demonstrated that SS rats show increased mRNA levels of various histone deacetylases that participate in gene regulation ( Cadet et al, 2016a ). In a subsequent report, we also documented that SR rats exhibited increases in nucleus accumbens proenkephalin and prodynorphin mRNA levels ( Cadet et al, 2016b ). Herein, we expand on our previous work by demonstrating that, in the dorsal striatum, neurotrophins and activation of their downstream signaling cascade distinguishes SS from SR phenotypes following prolonged abstinence from METH intake.…”
Section: Discussionmentioning
confidence: 71%